Social Capital and the Viability of Stakeholder-Oriented Firms: Evidence from Norwegian Savings Banks - Charlotte Ostergaard; Ibolya Schindele; Bent Vale (Norges Bank, 2009)
Stakeholder oriented governance systems are often thought to hamper efficiency. We show that social capital improves the viability of stakeholder-oriented firms in competitive markets. Studying exits from the population of Norwegian savings banks after deregulations, we find that banks located in communities with high social capital have a higher probability of survival. We propose that social capital facilitates collective decision-making, ensuring that banks internalize the preferences of the community in return for continued community patronage. Consistently, we find that in high social capital areas banks operate with lower interest rate margins, lower returns on assets, and lower loan losses.
hdl:11250/2497628
Keywords: Z13; P13; G34; G21; 330; stakeholder governance; social capital; nonprofit firms; corporate governance; financial intermediation